Agricultural Development Bank Reform - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
Agricultural development banks (AgDBs), which are not viable, should either be closed, or transformed into self-reliant, sustainable financial intermediaries. Experience shows that reform is possible. Among the prominent cases are Bank Rakyat Indonesia (BRI) and Bank for Agriculture and Agricultural Cooperatives (BAAC, Thailand) as well as ADB/Nepal, which has been transforming its small farmer credit program into financially self-reliant local financial intermediaries owned and managed by the poor. In Africa, many AgDBs have gone into liquidation; but there are some promising cases of reform, among them BNDA/Mali. Once the political will to reform has been generated, many more AgDBs have the potential of contributing to poverty alleviation through sustainable financial services. The successfully reformed institutions (i) mobilize their resources domestically while providing positive real returns to their depositors; (ii) have their loans repaid and their costs covered from the operational income; (iii) produce sufficient retained earnings to offset the erosion of their resources from inflation and to finance their expansion; and (iv) continually increase their saver and borrower outreach and the quality of their services to all segments of the rural population including the poor. To initiate and coordinate AgDB reform, the following is being proposed: (i) donor coordination and information exchange; (ii) preparation of a state-of-the-art report; (iii) case studies of ongoing AgDB reforms; (iv) conferences with regional agricultural credit associations (Afraca, Apraca, Nenaraca, Alide) to work out regional AgDB reform strategies; (v) feasibility studies of AgDB reform; (vi) implementation of AgDB reform with donor-coordinated support.
Keywords: 330; Landwirtschaftsbank; Reorganisation; Indonesien; Thailand; Nepal